Academic Reading: Comparing Students' and Faculty Perceptions of Its Value, Practice, and Pedagogy. Issue 3 (23rd June 2018) - Howard, Pamela J.; Gorzycki, Meg; Desa, Geoffrey; Allen, Diane D.
Abstract : This cross-sectional study at a four-year college explored the alignment between students' and faculty perceptions and behaviors regarding academic reading. Constructs from the academic reading literature were used to create a 10-item survey, modified slightly for faculty and students to respond to the same prompts. A convenience sample of 848 students and a snowball sample of 63 faculty examined the value of academic reading, academic reading practices, and attitudes toward academic reading pedagogy. Differences in agreement between students and faculty were statistically significant for all items. Students and faculty agree that undergraduate education should make students proficient academic readers, although the faculty mean is significantly higher than the students'. The expert-novice, Dunning-Kruger effect, and disengagement compact are three theories proposed to explain results.